Die wese van onderrig - Malan Nel (Verbum et Ecclesia)
The essence of teaching. This article is a reflection on significant empirical qualitative research done within four Afrikaans-speaking denominations in South Africa. The research was prompted by a request from one such denomination experiencing a serious challenge in what is called ‘kategese’ in Afrikaans-speaking Reformed churches. The process of registering a research project within the Department of Practical Theology and Mission Studies was done accordingly and the necessary ethical clearance was obtained. After 123 qualitative interviews and the scientific analysis of the data, it was decided to theologically reflect on the nine most outstanding concepts deriving from the analysis. This article has a twofold purpose: it describes the empirical research process; and secondly, it reflects theologically on the essence of the didache as a ministry.